2003
DOI: 10.1046/j.1460-9568.2003.02862.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized deficits in visual selective attention after V4 and TEO lesions in macaques

Abstract: To test the role of areas V4 and TEO in the attentional filtering of distracting information, we studied the effects of lesions in these areas, in monkeys discriminating target stimuli surrounded by irrelevant distracters. The lesions were restricted, such that a single visual field quadrant was affected by a V4 lesion alone, a TEO lesion alone, or a combined lesion in V4 and TEO, while one quadrant served as a normal control. The monkeys fixated a spot while discriminating the orientation, colour or motion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 103 publications
3
14
1
Order By: Relevance
“…This distribution of areas matches the network of visual processing areas as delineated by connectional anatomy studies of V4, PITd/TEO, FEF, and LIP (Andersen et al, 1990;Felleman and Van Essen, 1991;Distler et al, 1993;Schall et al, 1995;Lewis and Van Essen, 2000a;Ungerleider et al, 2007). Chemical deactivations and lesions of these visual processing areas lead to impairments in the discrimination of visual stimuli or in the allocation of visual attention (De Weerd et al, 1999;De Weerd et al, 2003;Wardak et al, 2004;Buffalo et al, 2005;Wardak et al, 2006;Rossi et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…This distribution of areas matches the network of visual processing areas as delineated by connectional anatomy studies of V4, PITd/TEO, FEF, and LIP (Andersen et al, 1990;Felleman and Van Essen, 1991;Distler et al, 1993;Schall et al, 1995;Lewis and Van Essen, 2000a;Ungerleider et al, 2007). Chemical deactivations and lesions of these visual processing areas lead to impairments in the discrimination of visual stimuli or in the allocation of visual attention (De Weerd et al, 1999;De Weerd et al, 2003;Wardak et al, 2004;Buffalo et al, 2005;Wardak et al, 2006;Rossi et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…Hence, the biasing signal influencing competition is modeled by a multiplicative increase in gain of all inputs provided by attended, but not by unattended, stimuli in the RF. Taken together, the data suggest that attention acts to boost the response to weak stimuli, which increases the probability to detect and correctly discriminate them (De Weerd, Desimone, & Ungerleider, 2003;Ress & Heeger, 2003;Gallant, Shoup, & Mazer, 2000;Reynolds, Pasternak, et al, 2000;De Weerd, Peralta III, Desimone, & Ungerleider, 1999;McAdams & Maunsell, 1999;Reynolds, Chelazzi, et al, 1999;Schiller & Lee, 1991). The idea of a multiplicative increase in the gain of excitatory and inhibitory inputs can also be used to explain the attention-induced increase in the probability of perceiving filling-in.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous physiological studies of monkey V4 have suggested that V4 is involved in a broad range of complex visual functions, not limited to one visual modality, including color, texture and form vision [48]. Lesions of V4 result in deficits in visual tasks that do not rely on a single visual modality [48], including in visual recognition [49] and in attentional processing [50]. The abundance of functional evidence suggesting a central role for V4 in the integration of information from different components of the visual system is consistent with its structural embedding as reported in this study.…”
Section: Discussionmentioning
confidence: 99%